Rupa Wujud Ragil Kuning dalam Rekonstruksi Narasi Tradisi Topeng Malangan sebagai Ikon Pengembangan Pariwisata Kampung Budaya Polowijen - Siti Zurinani; Fatmawati Fatmawati; Muh Fatoni Rohman (Endogami: Jurnal Ilmiah Kajian Antropologi, 2020)
Since 2016, the local government of Malang has opened 11 thematic villages tailored to each region's otential and uniqueness. Kampung Budaya Polowijen (Polowijen Cultural Village) was selected as the subject of this paper. The village presented a rich tradition and local histories, such as Malangan masks. The village also offered Mbah Reni mythology as its main tourist attraction. It used Mbah Reni in its historical framing and claimed that Polowijen mask art was the Malangan art of Malang city; thus, the discovery and strengthening Ragil Kuning mask of Polowijen cultural tradition are imperative to discuss. The researchers employed a qualitative descriptive method in this study. Panawijen's historical narrative and its cultural commodification of community needed to be explored and learned for its continued behavior.